Evaluating nutrition education interventions for medical students: A rapid review. Issue 5 (29th November 2021) - Patel, Priya; Kassam, Shireen
Abstract: Background: Unhealthy diets account for 20% of all deaths globally. Most medical schools do not sufficiently teach their students the clinical application of nutrition science. Evaluating the efficacy of nutrition education interventions is therefore important for their widespread implementation. Methods: A rapid review of the literature published between 2015 and 2020 was conducted to identify nutrition education interventions delivered to undergraduate medical students. The modified Kirkpatrick hierarchy score was used to evaluate the outcome measures. Study characteristics and outcomes were charted and discussed using narrative synthesis. Included studies were appraised using the MERSQI criteria. Results: Fifteen nutrition education interventions met the inclusion criteria. Twelve were from the USA and most were optional rather than compulsory. Interventions involved a mixture of methods including cooking sessions, lectures, and student‐led programs. The content covered was variable and the median duration was 11 h (range 90 min to 75 h). The modified Kirkpatrick scores varied and the median MERSQI score was 12.8/18. No studies reported the use of national or standardised guidance to inform the learning objectives of the interventions. Conclusions: The interventions reviewed are heterogenous in their nature and outcomes. This review highlights the advantages of utilising interprofessional learning, focusing on student's personal health behaviours and harnessing novel teaching methods such as hands‐on cooking. Using national guidance to develop learning outcomes will help to standardise the content taught. Future studies may aim to use validated assessment tools and investigate the long‐term impacts on delivery of care and patient outcomes. Key points: Increased nutrition training in medical education is needed. A variety of teaching approaches were identified, including novel methods such as culinary medicine and service learning. Future research is needed to further evaluate nutrition education interventions, including patient health outcomes. Development and utilisation of national guidance is needed to standardise content. Abstract : Globally, unhealthy diets contribute to approximately 20% of all deaths. A rapid review was conducted of nutrition education interventions published between 2015 and 2020 delivered to medical students, identifying 15 included studies. This review highlights the advantages of novel teaching methods and the need for content standardisation.